2023
DOI: 10.1001/jamaophthalmol.2023.2855
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose 0.01% Atropine Eye Drops vs Placebo for Myopia Control

Abstract: ImportanceControlling myopia progression is of interest worldwide. Low-dose atropine eye drops have slowed progression in children in East Asia.ObjectiveTo compare atropine, 0.01%, eye drops with placebo for slowing myopia progression in US children.Design, Setting, and ParticipantsThis was a randomized placebo-controlled, double-masked, clinical trial conducted from June 2018 to September 2022. Children aged 5 to 12 years were recruited from 12 community- and institution-based practices in the US. Participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 50 publications
0
29
1
Order By: Relevance
“…Zadnik et al also recently reported reduction in myopia progression in their secondary outcome of 0.01% atropine compared with placebo but not for the primary outcome of 0.02% atropine over 3 years of treatment. However, other similar randomized clinical trials by the National Eye Institute-sponsored Pediatric Eye Disease Investigator Group did not show a benefit of 0.01% atropine compared with placebo and suggested evaluation of the use of higher concentrations . While a Cochrane meta-analysis further supports that low dose atropine (less than 0.1%) had a mean treatment difference of 0.24 D with equivalence criteria being less than 0.25 D, these studies do not incorporate the recent lack of an effect for the primary 0.02% atropine trial by Zadnik et al nor the lack of an effect of the 0.01% atropine dose in the Pediatric Eye Disease Investigator Group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zadnik et al also recently reported reduction in myopia progression in their secondary outcome of 0.01% atropine compared with placebo but not for the primary outcome of 0.02% atropine over 3 years of treatment. However, other similar randomized clinical trials by the National Eye Institute-sponsored Pediatric Eye Disease Investigator Group did not show a benefit of 0.01% atropine compared with placebo and suggested evaluation of the use of higher concentrations . While a Cochrane meta-analysis further supports that low dose atropine (less than 0.1%) had a mean treatment difference of 0.24 D with equivalence criteria being less than 0.25 D, these studies do not incorporate the recent lack of an effect for the primary 0.02% atropine trial by Zadnik et al nor the lack of an effect of the 0.01% atropine dose in the Pediatric Eye Disease Investigator Group.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, topical administration of atropine eye drops has been demonstrated to be a safe and effective intervention in slowing the onset of myopia and reducing myopia progression in children . However, a recent clinical trial of 0.01% low-dose atropine eye drops did not slow myopia progression or axial elongation in US children . Additionally, a recent meta-analysis reported that low-dose (less than 0.1%) atropine met the equivalence criterion (less than 0.25 diopters [D]) showing a mean treatment difference of 0.24 D .…”
Section: Introductionmentioning
confidence: 99%
“…These initial study results led to the widespread administration and rapid adoption of nightly administration of low-dose atropine eye drops (0.01% to 0.05%) to young children with low myopia (−1 diopter [D] to −6 D) to slow progression of the myopia and axial elongation of the eye. More recently completed studies in Australia, North American, and Europe have found smaller or no effects of the low concentrations studied (0.01% and 0.02%) in terms of slowing myopia progression . Each of these randomized clinical trials was launched recognizing that the primary and secondary outcomes would necessarily be short term and thus would be unable to provide the long-term outcomes needed to completely assess efficacy and safety.…”
mentioning
confidence: 99%
“…Nonetheless, the observation of increased risks for MMD with atropine concentrations of 0.1% and 0.5% deserves additional research. Of note, the 0.01% concentration used in many current studies did not show any increase in adverse events …”
mentioning
confidence: 99%
“…To assist with these challenges, beginning in 2024, the JAMA Ophthalmology editors are inviting experts to help synthesize such topics relevant to ophthalmology within succinct, relatively short summaries that follow the examples of JAMA Insights, JAMA Clinical Evidence Synopsis , and JAMA Clinical Guidelines Synopses . For example, 2 of the top 3 articles by views/downloads in 2023 (Table) were randomized clinical trials evaluating the potential risks and benefits of low-dose atropine eye drops vs placebo for myopia control. The goal of these educational initiatives will be to provide pithy evaluations across clinical trials like these for the busy reader and to synthesize new information rapidly that might change clinical practice in a way that is complementary to reviews, book chapters, or more extensive guidelines.…”
mentioning
confidence: 99%